Dipeptide derivatives of AZT: Synthesis, chemical stability, activation in human plasma, hPEPT1 affinity, and antiviral activity - Cledir Santos (2008)
5'-O-Dipeptide ester prodrugs of antiviral zidovudine (AZT) were designed to target the human intestinal oligopeptide transporter, hPEPT1, and were evaluated for their stability at pH 74 in buffer and in human plasma, affinity toward hPEPT1, cytotoxicity, and antiretroviral activity. The dipeptide esters of AZT undergo cyclization in buffer at pH 7.4 to release the parent drug at a rate that depends on the size of the side chains of the peptide carrier; the prodrug is considerably more stable if bulky beta-branched amino acids such as IIe and Val are present, particularly as C-terminal residues. Incubation in human plasma showed that most of the dipeptide esters of AZT release the parent drug through two aminopeptidase-mediated pathways: 1) stepwise cleavage of each of the amino acids and 2) direct cleavage of the dipeptide-drug ester bond. However, the plasma hydrolysis of Gly-Gly-AZT and Phe-Gly-AZT showed only direct cleavage of the dipeptide-drug ester bond. Substrate half-lives in plasma were again remarkably high when hydrophobic beta-bronched amino acids (Val, lie) were present. The esters were also good substrates for the intestinal oligopeptide transporter hPEPT1 in vitro, with Val-Gly-AZT and Val-Ala-AZT presenting the highest affinity toward the transporter (IC(50): 0.20 and 0.15 mM, respectively). The AZT dipeptide esters were assayed against the IIIB and ROD strains of HIV, and their cytotoxicity was evaluated in MT-4 cells. The selectivity index of the prodrugs was two- to threefold higher than that of AZT for all compounds analyzed. These results point to the potential of dipeptide-based carriers for the development of effective antiviral drug-delivery systems. Val-Ala-AZT appears to combine chemical stability with good affinity for the hPEPT1 transporter and on improved cytotoxicity/antiretroviral index relative to AZT.